Evaluation in Alabio duck (Anas plathyrhincos Borneo) of soluble protein, protein digestibility, metabolizable energy and nitrogen retention of freshwater snail flesh (Pomacea paludosa) incubated with bromelain enzyme for different times and concentration - Dharmawati, Siti; hartutik, Hartutik; Natsir, Muhammad Halim; Sjofjan, Osfar (Agriculture and Natural Resources, 2023)
Importance of the work: Metabolizable energy of feed is the remaining energy from feed after losing in urine and feces. As such, it is a useful parameter for improving feed performance. However, duckspecific information regarding the metabolizable energy and protein digestibility of freshwater snails is still limited. Objectives: To evaluate in Alabio duck the soluble protein and protein digestibility, nitrogen retention, and metabolizable energy of freshwater snail flesh incubated with bromelain enzyme in difference incubation and concentration. Materials and Methods: Freshwater snail flesh was incubated with bromelain enzyme (1%, 2%, 3%, or 4%) for varying durations (1, 2, 3, or 4 hours). The treated flesh was then fed to Alabio ducks using a factorial design in a completely randomized design with five replications (one duck/replication) Results: The highest values for soluble protein (6.58 ± 1.87%), protein digestibility (87.79±0.06%), nitrogen retention (90.35±0.01%), apparent metabolizable energy (3,492.86±9.48 kcal/kg) and N-corrected metabolizable energy (3,491.03±9.47) were obtained in snail flesh incubated with 3% bromelain enzyme for 3 hr. Main finding: Bromelain enzyme at 3% concentration with 3-hour incubation demonstrated superior outcomes, including increased soluble protein, protein digestibility, nitrogen retention, apparent metabolizable energy, and N-corrected metabolizable energy. This enzyme mixture holds promise for application in poultry feed formulations.